Edible sprouts: Nutritional quality, microbiological safety and potential application in new products (Research, Society and Development, 2022)
Edible sprouts are a good source of nutrients and have been consumed for about 5000 years by the people of the East, and can be obtained in a few days after germination, which requires little space and inputs. Thus, the present work sought to verify the main bioactive compounds present in different types of edible sprouts, the influence of germination on the content of these compounds, the main organisms associated with contamination by these foods and their potential application for the development of new products. For this, an integrative literature review was developed, with articles published in the Web of Science, Scopus, Google Scholar and Scielo databases. It was identified that the main bioactive compounds in these foods are phenolic compounds, glucosinolates, vitamin (C, B, E and D), minerals (Ca+2, Mg+2, K+, Na+, Fe+2, Zn+2, Cu+2 and Mn+2) and aminobutyric acid. The studies that applied treatments such as ultrasound election, jasmonic acid (JA), NaCl and glucose solutions, an increase in the content of bioactive compounds present in the sprouts was observed. Regarding the main microorganisms associated with contamination by these foods, they are pathogens such as Salmonella spp., Escherichia coli and Staphylococcus aureus, but with the application of physical treatments such as bleaching, ultrasound, cooling and irradiation, and based on chemical reagents such as methyl jasmonate (JA), salicylic acid and tocopherol, proved to be effective in controlling these microorganisms. Finally, the sprouts were applied with the aim of nutritionally enriching products such as pasta and beverages.